2023
DOI: 10.1177/09637214231206095
|View full text |Cite
|
Sign up to set email alerts
|

Parenting by Lying

Peipei Setoh,
Petrina Hui Xian Low,
Gail D. Heyman
et al.

Abstract: Parenting by lying is a practice in which parents lie to their children to influence their emotions or behavior. Recently, researchers have tried to document the nature of this phenomenon and to understand its causes and consequences. The present research provides an overview of the research in the emerging field, describes some key theoretical and methodological challenges in studying this topic, and proposes a theoretical framework for understanding parenting by lying and for guiding future research to advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Together, empirical studies on day-to-day parental lying have identified various correlates, both potential determinants and outcomes, at different levels (i.e., parent, child, and the family context). Setoh et al (2024) provide in their scoping review an overview of research on parenting by lying, specifically. However, following the theoretical and empirical framework described above, we have reason to believe that other forms and types of parental lying, and not only parenting by lying, may be relevant and meaningful in child development, parenting practices and family functioning as well.…”
Section: Theoretical Framework: An Ecological Perspective On Parental...mentioning
confidence: 99%
See 2 more Smart Citations
“…Together, empirical studies on day-to-day parental lying have identified various correlates, both potential determinants and outcomes, at different levels (i.e., parent, child, and the family context). Setoh et al (2024) provide in their scoping review an overview of research on parenting by lying, specifically. However, following the theoretical and empirical framework described above, we have reason to believe that other forms and types of parental lying, and not only parenting by lying, may be relevant and meaningful in child development, parenting practices and family functioning as well.…”
Section: Theoretical Framework: An Ecological Perspective On Parental...mentioning
confidence: 99%
“…This systematic review was built on the scoping review of Setoh et al (2024) on parenting by lying, one specific type of parental lying. Hence, we aimed to provide a comprehensive overview of the current body of literature on parental lying and all its potential manifestations.…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation